Paracetamol as a basic component of a modern approach to adequate perioperative analgesia - Zakalska, Khrystyna; Babiichuk, O (Pain medicine, 2020)
The problem of adequate perioperative anesthesia is one of the most pressing in the current health care system, given its medical, humanistic and socio-economic aspects. Currently, the standard of postoperative analgesia is multimodal analgesia (MMA). One of the major and required components of MMA is paracetamol, which has antipyretic and analgesic effects with limited peripheral anti-inflammatory activity. Most authors consider intravenous paracetamol as a base drug in a multimodal analgesia strategy for a variety of surgical interventions, which reduces the need for opioids and reduces the side effects of the latter, which in turn significantly affects the results of treatment and the length of hospital stay. Numerous studies in many countries have created a broad evidence base for the clinical use of this drug. Due to its pharmacokinetic and pharmacodynamic properties, it has been shown that intravenous paracetamol has several advantages over oral and rectal forms: early and more effective onset of analgesia and stable maintenance of the therapeutic dose of paracetamol are explained by the formation of a faster and higher peak in the concentration of the drug. The side effects of using paracetamol can be compared with placebo. The mechanism of action of the drug is different from the mechanism of action of NSAIDs, however, is still not fully understood. It may possibly involve inhibition of cyclooxygenase, cannabinoid, or nitric oxide pathways in the central nervous system. Intravenous paracetamol is a safe and effective first-line drug for the treatment of moderate pain in the perioperative period.